Subarea Description and Breakage Constitutive Model of Rock Mass Based on CT Test - Yao Zhang; Chenghao Chen; Xiaotao Yin; Jiadong Chen (Buildings, 2022)
Based on CT experiments of the mechanical behavior of a certain sandstone, the safety zone, the damaging zone, and the fracture zone of geotechnical materials were defined, and the CT threshold standard of this zone was discussed and empirically selected. Mathematical morphological image measurement technology was used to analyze the CT information of each section, and the variation law of the sandstone CT number with the loading process and the conditions of the damaging zone was studied. According to the statistical results of the CT number of the safety zone, the damaging zone, and the fracture zone obtained at each loading stage, a statistical-damage variable based on the CT number was defined, and the equation of the damage evolution pertinent to this damage variable was established. On the basis of all these data, a constitutive model that can reflect the divisional damage-fracture of sandstone was constructed. The theoretical stress–strain curve and the measured curve were well fitted, demonstrating that the improved constitutive model could accurately reflect the failure of sandstone partitions. A qualitative analysis of CT scans and a quantitative analysis of the constitutive model were combined in this experiment, which has a certain reference value for the development of geotechnical engineering experiments.